2024
DOI: 10.3389/fmicb.2024.1336387
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of carbapenem-resistance in Gram-negative isolates obtained from clinical samples at Jimma Medical Center, Ethiopia

Mulatu Gashaw,
Esayas Kebede Gudina,
Solomon Ali
et al.

Abstract: BackgroundIn resource-constrained settings, limited antibiotic options make treating carbapenem-resistant bacterial infections difficult for healthcare providers. This study aimed to assess carbapenemase expression in Gram-negative bacteria isolated from clinical samples in Jimma, Ethiopia.MethodsA cross-sectional study was conducted to assess carbapenemase expression in Gram-negative bacteria isolated from patients attending Jimma Medical Center. Totally, 846 Gram-negative bacteria were isolated and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Resistance in CRPA isolates that do not produce carbapenemases could be mediated by a loss of porin D (OprD) and/or overexpression of efflux pumps (such as MexAB-OprM) (Amsalu et al, 2020; Arzanlou et al, 2017; Gashaw et al, 2024; Nieto-Saucedo et al, 2023). OprD is an outer membrane porin in P. aeruginosa that facilitates the uptake of basic amino acids and imipenem (Alcock et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Resistance in CRPA isolates that do not produce carbapenemases could be mediated by a loss of porin D (OprD) and/or overexpression of efflux pumps (such as MexAB-OprM) (Amsalu et al, 2020; Arzanlou et al, 2017; Gashaw et al, 2024; Nieto-Saucedo et al, 2023). OprD is an outer membrane porin in P. aeruginosa that facilitates the uptake of basic amino acids and imipenem (Alcock et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies conducted in the same study area have reported a high prevalence of ESBL-producing bacteria and carbapenem-resistant strains among Gram-negative bacteria isolated from clinical samples [13][14][15][16][17]. The prevalence rates for ESBL producers range from 50 to 80%, while carbapenem-resistant strains range from 10 to 20% [13][14][15][16][17]. Notably, ESBL production is commonly observed in bacteria such as E. coli, K. pneumoniae, K. variicola, E. cloacae, and many others [14,15,17].…”
Section: Introductionmentioning
confidence: 86%
“…The prevalence rates for ESBL producers range from 50 to 80%, while carbapenem-resistant strains range from 10 to 20% [13][14][15][16][17]. Notably, ESBL production is commonly observed in bacteria such as E. coli, K. pneumoniae, K. variicola, E. cloacae, and many others [14,15,17]. Similarly, the emergence of carbapenem resistance is frequently detected in Gram-negative bacteria such as A. baumannii, P. aeruginosa, E. coli, and K. pneumoniae [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging resistance of GNB to colistin, the drug of last resort, is very alarming. There need to be proper detection methods that can help in the rapid and reliable identification and characterization of resistant bacteria isolated from clinical or environmental settings [135,136]. Here, we have tried to summarize the different phenotypic as well as molecular methods that are most commonly used to detect colistin-resistant GNB.…”
Section: Phenotypic and Molecular Detection Methods Of Colistin-resis...mentioning
confidence: 99%